2016
DOI: 10.1007/s10578-016-0640-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Reactive–Proactive Aggression and Anxiety Sensitivity with Internalizing and Externalizing Symptoms in Children with Attention-Deficit/Hyperactivity Disorder

Abstract: This study evaluates the associations among the symptoms of anxiety, depression, and disruptive behavioral disorders (DBD) in the context of their relationships with reactive-proactive aggression and anxiety sensitivity in children with attention-deficit/hyperactivity disorder (ADHD). The sample consisted of 342 treatment-naive children with ADHD. The severity of ADHD and DBD symptoms were assessed via parent- and teacher-rated inventories. Anxiety sensitivity, reactive-proactive aggression and severity of anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Consistent with Drabick et al’s (2010) model, there is evidence that co-occurring anxiety increases the concurrent risk for CPs in children with ADHD. When anxiety was assessed via rating scale, Bilgic et al (2017; see above) found a relationship between anxiety scores and reactive aggression, but not proactive aggression. In a school-based sample of children with ADHD, Pollack, Hojnoski, DuPaul, and Kern (2016) found that compared with children with ADHD alone, children with ADHD and ANX had more behavioral problems as assessed by the Social Skills Rating System.…”
Section: Co-occurring Anxiety Exacerbates Cpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with Drabick et al’s (2010) model, there is evidence that co-occurring anxiety increases the concurrent risk for CPs in children with ADHD. When anxiety was assessed via rating scale, Bilgic et al (2017; see above) found a relationship between anxiety scores and reactive aggression, but not proactive aggression. In a school-based sample of children with ADHD, Pollack, Hojnoski, DuPaul, and Kern (2016) found that compared with children with ADHD alone, children with ADHD and ANX had more behavioral problems as assessed by the Social Skills Rating System.…”
Section: Co-occurring Anxiety Exacerbates Cpsmentioning
confidence: 99%
“…In support of this position, some research that compared children diagnosed with ADHD with children diagnosed with ADHD co-occurring with ANX disorders reported that children diagnosed with ADHD and co-occurring ANX disorders were less aggressive than children who were diagnosed with ADHD without anxiety (Connor, Chartier, Preen, & Kaplan, 2010; Falk, Lee, & Chorpita, 2015) This led the authors to, respectively, suggest that “co-morbid anxiety may confer a protective effect on aggression in ADHD youth” (Connor et al, 2010, p. 124), and “anxiety may attenuate the relationship between ADHD and overt aggression” (Falk et al, p. 6). A pair of recent studies (Bilgic et al 2017; Bilgic et al, 2013) found that among children with ADHD, anxiety sensitivity had a negative predictive influence on CD and perhaps ODD. Earlier research found that children with co-occurring ADHD and ANX were less frequently diagnosed with CD (Pliszka, 1989).…”
Section: Co-occurring Anxiety Attenuates Cpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in elementary school students, relational and physical aggression were suggested as the strongest predictors of anxiety [9]; in addition, a study on American 2nd, 3rd, and 4th graders demonstrated a relationship between baseline anxiety symptoms and higher levels of relational aggression over a 1-year period [10]. Furthermore, a study including children with attention-deficit/hyperactivity disorder reported that disruptive behavioral disorders were associated with reactive–proactive aggression and anxiety sensitivity [11]. While these studies provide insight regarding childhood aggression and anxiety, they focus on relatively young children (in their elementary school years or younger), making it difficult to apply them to adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…23 Externalizing disorders, such as oppositional defiant disorder and conduct disorder, are common in these teens and add to their daily challenges. 24 In such cases it is important to address ADHD as well as comorbidities since failure to adequately address both can lead to treatment failure. 25,26 The psychosocial difficulties these patients experience over the course of their adolescent years impair their functioning and treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%